2008
DOI: 10.1371/journal.pone.0003088
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomics Identifies Five Medulloblastoma Subtypes with Distinct Genetic Profiles, Pathway Signatures and Clinicopathological Features

Abstract: BackgroundMedulloblastoma is the most common malignant brain tumor in children. Despite recent improvements in cure rates, prediction of disease outcome remains a major challenge and survivors suffer from serious therapy-related side-effects. Recent data showed that patients with WNT-activated tumors have a favorable prognosis, suggesting that these patients could be treated less intensively, thereby reducing the side-effects. This illustrates the potential benefits of a robust classification of medulloblastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
725
2
15

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 640 publications
(794 citation statements)
references
References 58 publications
52
725
2
15
Order By: Relevance
“…Functional genomic platforms have reproducibly shown that medulloblastoma can be categorized into four molecular subclasses that are distinct in terms of both prognosis and predicted therapeutic responses (Pomeroy et al, 2002;Thompson et al, 2006;Kool et al, 2008;Northcott et al, 2010). Medulloblastoma subtypes A and B are characterized by exclusive aberrant activation of the Wnt and Shh signaling pathways, respectively.…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional genomic platforms have reproducibly shown that medulloblastoma can be categorized into four molecular subclasses that are distinct in terms of both prognosis and predicted therapeutic responses (Pomeroy et al, 2002;Thompson et al, 2006;Kool et al, 2008;Northcott et al, 2010). Medulloblastoma subtypes A and B are characterized by exclusive aberrant activation of the Wnt and Shh signaling pathways, respectively.…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 99%
“…Given current efforts toward the molecular characterization of medulloblastomas into distinct subtypes (Pomeroy et al, 2002;Thompson et al, 2006;Kool et al, 2008;Northcott et al, 2010), we were interested to see if Bmi1 is implicated in any particular molecular subgroup of medulloblastomas. Although Bmi1 expression is elevated across all medulloblastoma molecular subtypes, its levels are highest in the most aggressive subtypes of medulloblastoma, groups C and D. These subtypes are associated with poor survival and invasive metastatic disease, and they remain refractory to current treatment modalities.…”
Section: Shh Regulates Bmi1 In Medulloblastoma Bticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain of chromosome 1q is a negative prognostic marker for survival also in medulloblastoma [57], but so far no correlation to the expression of Mcl-1 has been reported. Survivin is encoded by a single-copy gene located on human chromosome 17q25, a region that is frequently gained in unfavourable medulloblastoma and highrisk neuroblastoma [58][59][60]. Moreover, elevated expression of survivin is highly correlated to poor survival in both medulloblastoma and neuroblastoma (Fig.…”
Section: Deregulation Of the Intrinsic Apoptotic Pathwaymentioning
confidence: 99%
“…Recently, molecular studies have demonstrated that MB is not a single disease, but comprises a collection of four distinct molecular subgroups (Cho et al 2011;Kool et al 2008;Northcott et al 2011;Remke et al 2011a, b;Thompson et al 2006). Two of these subgroups are characterized by either activated WNT or SHH signaling, consistently show the most distinct genetic profiles, and remain Non-WNT/Non-SHH tumors named Group 3 and Group 4.…”
Section: Introductionmentioning
confidence: 99%